Pengembangan Asesmen Higher Order Thinking Skills (HOTS) Berbasis Computer Based Test (CBT) pada Materi Induksi Elektromagnetik - Bayu Pranata; Agus Suyatna; Undang Rosidin (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2020)
The research objective was to produce assessment product for Higher Order Thinking Skills (HOTS) using Computer Based Test (CBT) with four types of HOTS questions (true or false, multiple choices, fill in the blank and matching). It applied the basis of factual, conceptual, procedural and metacognitive-knowledge dimensions with illustrations in the form of discourse, images, graphics, videos, animation and interactive stimulation and feedback after going through the stages of logical validation, empirical validation and respondent questionnaires. Assessment product HOTS using CBT was implemented to Senior High School students in the learning process of physics subject through R&D research steps proposed by Borg and Gall that aimed to stimulate higher-order thinking skills. This is a development research in which the method was conducted by giving HOTS test questions using CBT to measure students’ HOTS profiles and distributing practical questionnaires related to students’ perceptions toward assessment products of HOTS using CBT. The data collection technique was carried out using expert validation sheet and respondent questionnaire. Then, the collected data was analyzed in descriptive quantitative. The analysis showed that the logical validity obtained from expert validation on HOTS assessment using CBT was 81% with a valid category. Empirical validity was obtained from students’ HOTS test results using CBT which showed that the four types of questions were able to measure students’ HOTS. In addition, students’ responses on practical aspects were 86.75% with a very practical category. The results of the data showed that the development of assessment product of HOTS using CBT in electromagnetic induction material for Physics subject in Senior High School is already valid and practical. Thus, it was concluded that the development of HOTS assessment using CBT has already contained the right stimulus and is able to encourage students to think using HOTS.